Self-esteem and relationship status in a system of interpersonal relations in a group of younger teenagers - Pomatsalyuk, A.R. (ХНУ імені В.Н. Каразіна, 2012)
The adolescent status in a system of personal relationships is a major precondition for the formation of personality. This article considers the concept of the interaction of an individual and the community, describes the personal characteristics of adolescents with different status position in the group.
Статус подростка в системе личных взаимоотношений является серьезной предпосылкой формирования его личности. В данной статье рассматривается представление о взаимодействии личности и коллектива, описываются личностные характеристики подростков, имеющих различное статусное положение в группе.
Keywords: adolescents; group; peers; personality; relationships; status